Analisis Lingkungan Kerja Dan Pengawasan Terhadap Kepuasan Kerja Pegawai Kantor Camat Talang Empat Kabupaten Bengkulu Tengah - Kasdi, By; Hartono, Rudi (Jurnal Adminitrasi Bisnis Nusantara, 2022)
The aim of this research is to determine the relationship between work environment and job satisfaction of office workers in Talang Empat district in Bengkulu Tenga province and determine the relationship between supervision and job satisfaction. office workers from Talang Empat District to Bengkulu Central District Party Committee. Nowadays, the management aspect of an organization is necessary to achieve the goals of the organization optimally. Monitoring is one of the management functions that must be performed to ensure that the implementation of activities is in accordance with the established plans to achieve the objectives. In addition to trying to create a good working environment for employees working there, creating a feeling of comfort and enjoyment for employees, this can be seen by the existence of adequate and clean facilities. in the workplace and colleagues can support each other and can communicate well to increase employee job satisfaction The type of research used is explanatory research. Research results on the relationship between work environment and employee job satisfaction with the Spearman rank correlation value of 0.692 is a close relationship because it is in the range of 0.600 0.799 and the hypothesis test the theory has a significant value of 0.002 etlt; 0.05 H01 Rejected Ha1 Accepted This means that work environment has a significant relationship with job satisfaction of Talang Empat District Headquarters, Bengkulu District Center. Although the results of the study show that there is a significant relationship between supervision and employee job satisfaction with a Spearman rank correlation value of 0.750, this is a close relationship because it is located in the range of 0.600 0.799 and hypothesis testing is known to have a value of 0.001 etlt; 0.05 for H02 is eliminated. Ha2 is accepted